Effect of a vertical half cylinder on swimming of silver carp, Hypophthalmichthys molitrix: Implications for microhabitat restoration and fishway design. (14th March 2019) - Ke, Senfan; Li, Zhimin; Jiang, Zewen; Goerig, Elsa; Kynard, Boyd; Liu, Defu; Shi, Xiaotao
Abstract: In recent years, the relationship between hydraulics associated with the substrate and fish swimming behaviour has become increasingly important to the design of microhabitat around substrates for river restoration. To better understand the hydraulics associated with substrate on fish swimming, we studied the effects of a vertical half cylinder (hereafter, cylinder) on the critical swimming speed of juvenile silver carp ( Hypophthalmichthys molitrix ). Absolute and relative critical swimming speeds of fish in the flow field of the cylinder were significantly increased compared with those swimming in free flow. In addition, the amplitude of fish head and tail oscillations were significantly greater in flows created by the half cylinder. This study highlights the importance of roughness elements in stream microhabitat restoration and, possibly, for fishway design.